STUDY OF TANNING SUBSTANCES AND FLAVANOIDS IN THE LEAVES OF ASIAN AGRIMONY (AGRIMONIA ASIATICA JUZ.) (Eurasian Journal of Ecology, 2024)
Asian agrimony (Agrimonia asiatica Juz) is a common wild plant including that growing within the territory of Kazakhstan, a very promising raw material for flavonoids and tanning substances release. These active substances have significant pharmacological potential. The article presents the results of work on determining the quantitative and qualitative composition of tannins and flavonoids in plant raw materials from the Asian agrimony (Agrimonia asiatica Juz). The presence of tanning substances and flavonoids in the extracts received from the above-ground part of Asian agrimony has been established by qualitative reactions. Various developers for paper chromatography have been used. The quantitative determination of flavonoids has been carried out in terms of the equivalent amount of quercetine, and the standard method of permanganatometric titration has been used to determine the quantitative content of tanning substances. Quantitative content of tanning substances in the leaves of Asian agrimony (A. asiatica juz.) showed an 8,156 %, and a quantitative content of flavonoids showed 1,9 %. The purpose of the study is to determine the quantitative and qualitative composition of tannins and flavanoids in prepared herbal medicinal raw materials in order to identify the most promising objects for further research.Keywords: Asian agrimony (Agrimonia asiatica Juz), tanning substances, flavonoids, phytochemistry